Observational assessment of forceful exertion and the perceived force demands of daily activities. - Marshall MM; Armstrong TJ (Journal of Occupational Rehabilitation, 2004)
The primary objective of this study was to assess the accuracy and precision with which analysts observe and estimate the force produced as subjects performed exertions on a work simulator. Eight analysts observed 32 subjects and estimated force as a percent of subjects' maximum voluntary contraction (% MVC). Analysts exhibited bias toward the mean, as high force exertions (> 67% MVC) were underestimated (mean: 11.6% MVC) and low force exertions (<34% MVC) were overestimated (mean: 6.7% MVC). Average error for medium force exertions (34-67% MVC) was not statistically different from zero (2.1% MVC). For all force levels, precision of the estimate was very poor (standard deviation range: 16.2-20.7% MVC). Experience of the analyst in performing ergonomic analysis did not affect accuracy. A secondary objective of the study was to conduct a survey in which subjects identified activities of daily living they perceived as equivalent to controlled force levels. A total of 59 different activities ranging from minimal force required to near maximum were listed by at least 5% of the participants. This list may be used to assist health care practitioners and patients convey the force demands required of occupational tasks as well as for evaluating the diminished strength of the patient.